A Study on Consumer Buying Behaviour towards Eatery Outlets in Silvassa City - Neha Kataria; Pandey, Rajesh Kumar (Management Journal for Advanced Research, 2023)
The Indian food joint industry has witnessed high growth strides in the past years, with increasing disposable income, exposure to a number of cuisines and consumers’ willingness to experiment a mix of both western and local menu. The purpose of the research is to study consumer buying behaviour towards food eatery outlets with respect to Silvassa city. The article aims to perceive the consumption pattern towards food joint; the likes, dislikes and perception and preferences of consumers towards eatery outlets. The article will contain issues regarding place of purchase and the factors determining the behaviour of buyers of food products as well as factors affecting preferences of buyers of eatery services. The main aim of the study is to understand the concept, significance & process of consumer buying behaviour, to analyse the consumers’ buying behaviour towards eatery outlets in Silvassa city and to gather inferences from the study and extend recommendation with respect to the impact of consumer buying behaviour on business of Eatery Outlets. The research design is exploratory and descriptive and the data collected was primary and secondary using questionnaire as research instrument. The sample size is 121 and the population is residents from Silvassa city. The sampling technique used is non -probability convenience sampling. The scope of the study states the extent of Consumer Behaviour attributes is gathered in Silvassa City only. The Project enables to characterize the 7 Ps pertaining to the Eatery Outlets. The respondents hesitated to respond as the survey intended to ask their personal choices. The behavioural context is gathered from a limited area; hence the inferences are indicative in nature.